Scavenging of Dickkopf-1 by macromer-based biomaterials covalently decorated with sulfated hyaluronan displays pro-osteogenic effects. (15th September 2020) - Gronbach, M.; Mitrach, F.; Lidzba, V.; Müller, B.; Möller, S.; Rother, S.; Salbach-Hirsch, J.; Hofbauer, L.C.; Schnabelrauch, M.; Hintze, V.; Hacker, M.C.; Schulz-Siegmund, M.
Abstract: Dickkopf-1 (DKK1), a Wnt inhibitor secreted by bone marrow stromal cells (MSC), is known to play an important role in long-term non-union bone fracture defects and glucocorticoid induced osteoporosis. Mitigating its effects in early bone defects could improve osteogenesis and bone defect healing. Here, we applied a biomaterial strategy to deplete a defect environment from DKK1 by scavenging the protein via a macromer-based biomaterial covalently decorated with sulfated hyaluronan (sHA3). The material consisted of cross-copolymerized three-armed macromers with a small anchor molecule. Using the glycidyl anchor, polyetheramine (ED900) could be grafted to the material to which sHA3 was efficiently coupled in a separate step. For thorough investigation of material modification, flat material surfaces were generated by fabricating them on glass discs. The binding capability of sHA3 for DKK1 was demonstrated in this study by surface plasmon resonance measurements. Furthermore, the surfaces demonstrated the ability to scavenge and inactivate pathologic amounts of DKK1 from complex media. In a combinatory approach with Wnt3a, we were able to demonstrate that DKK1 is the preferred binding partner of our sHA3-functionalized surfaces. We validated our findings in a complex in vitro setting of differentiating SaOS-2 cells and primary hMSC. Here, endogenous DKK-1 was scavenged resulting in increased osteogenic differentiation indicating that this is a consistent biological effect irrespective of the model system used. Our study provides insights in the mechanisms and efficiency of sHA3 surface functionalization for DKK1 scavenging, which may be used in a clinical context in the future. Statement of Significance: Delayed bone defect healing has been shown to depend on the interplay of Wnt agonists and antagonists. In this study, we engineered surfaces of macromer materials via cross-copolymerization of a three-armed biodegradable macromer and a small anchor molecule (Glycidylmethacrylate). This material was stepwise modified with polyetheramines and sulfated hyaluronan (sHA3) in order to positively affect the bone healing micromilieu. We show that autocrine regulated pro-osteoclastic Wnt antagonist DKK1 and pro-osteoblastic agonist Wnt-3a were produced by SaOS-2 cells and hMSC. DKK1 was scavenged and inactivated from the micromilieu of osteogenic cells, whereas Wnt-3a remained unchanged in presence of DKK1. hMSC seeded and differentiated on sHA3 decorated macromer material showed improved osteogenic differentiation as measured by ALP activity and matrix mineralization. Graphical abstract: Image, graphical abstract